Storing short single-photon-level optical pulses in Bose–Einstein condensates for high-performance quantum memory. (13th April 2021) - Saglamyurek, Erhan; Hrushevskyi, Taras; Rastogi, Anindya; Cooke, Logan W; Smith, Benjamin D; LeBlanc, Lindsay J
Abstract: Large-scale quantum networks require quantum memories featuring long-lived storage of non-classical light together with efficient, high-speed and reliable operation. The concurrent realization of these features is challenging due to inherent limitations of matter platforms and light–matter interaction protocols. Here, we propose an approach to overcome this obstacle, based on the implementation of the Autler–Townes-splitting (ATS) quantum-memory protocol on Bose–Einstein condensate (BEC) platform. We demonstrate a proof-of-principle of this approach by storing short pulses of single-photon-level light as a collective spin-excitation in a rubidium-BEC. For 20 ns long-pulses, we achieve an ultra-low-noise memory with an efficiency of 30% and lifetime of 15 μ s. The non-adiabatic character of the ATS protocol (leading to high-speed and low-noise operation) in combination with the intrinsically large atomic densities and ultra-low temperatures of the BEC platform (offering highly efficient and long-lived storage) opens up a new avenue toward high-performance quantum memories.